The Physcomitrella patens chromosome‐scale assembly reveals moss genome structure and evolution. (19th January 2018) - Lang, Daniel; Ullrich, Kristian K.; Murat, Florent; Fuchs, Jörg; Jenkins, Jerry; Haas, Fabian B.; Piednoel, Mathieu; Gundlach, Heidrun; Van Bel, Michiel; Meyberg, Rabea; Vives, Cristina; Morata, Jordi; et al.
Summary: The draft genome of the moss model, Physcomitrella patens, comprised approximately 2000 unordered scaffolds. In order to enable analyses of genome structure and evolution we generated a chromosome‐scale genome assembly using genetic linkage as well as (end) sequencing of long DNA fragments. We find that 57% of the genome comprises transposable elements (TEs), some of which may be actively transposing during the life cycle. Unlike in flowering plant genomes, gene‐ and TE‐rich regions show an overall even distribution along the chromosomes. However, the chromosomes are mono‐centric with peaks of a class of Copia elements potentially coinciding with centromeres. Gene body methylation is evident in 5.7% of the protein‐coding genes, typically coinciding with low GC and low expression. Some giant virus insertions are transcriptionally active and might protect gametes from viral infection via siRNA mediated silencing. Structure‐based detection methods show that the genome evolved via two rounds of whole genome duplications (WGDs), apparently common in mosses but not in liverworts and hornworts. Several hundred genes are present in colinear regions conserved since the last common ancestor of plants. These syntenic regions are enriched for functions related to plant‐specific cell growth and tissue organization. The P . patens genome lacks the TE‐rich pericentromeric and gene‐rich distal regions typical for most flowering plant genomes. More non‐seed plant genomes are needed to unravel how plant genomes evolve, and to understand whether the P . patens genome structure is typical for mosses or bryophytes.